Exosomes from osteoarthritic fibroblast-like synoviocytes promote cartilage ferroptosis and damage via delivering microRNA-19b-3p to target SLC7A11 in osteoarthritis - Kong, Ruina; Ji, Lianmei; Pang, Yafei; Zhao, Dongbao; Gao, Jie (Frontiers in Immunology, 2023)
Objective Our previous studies revealed that normal synovial exosomes promoted chondrogenesis, and microRNA (miR)-19b-3p independently related to osteoarthritis (OA) risk. Subsequently, this study intended to further explore the effect of OA fibroblast-like synoviocyte (OA-FLS) exosomal miR-19b-3p on OA ferroptosis and its potential mechanisms. Methods Interleukin (IL)-1β-stimulated chondrocytes and medial meniscus surgery were used to construct the OA cellular model and the OA rat model, respectively. OA-FLS exosomes with/without miR-19b-3p modification were added to the IL-1β-stimulated chondrocytes and OA rat models, followed by direct miR-19b-3p mimic/inhibitor transfection with/without SLC7A11 overexpression plasmids. miR-19b-3p, ferroptosis-related markers (malondialdehyde (MDA), glutathione (GSH)/oxidized glutathione (GSSG), ferrous ion (Fe2+), glutathione peroxidase 4 (GPX4), solute carrier family 7 member 11 (SLC7A11), and acyl-CoA synthetase long-chain family member 4 (ACSL4)), mitochondrial membrane potential (MMP), and reactive oxygen species (ROS) levels were detected. Results Enhanced ferroptosis reflected by dysregulated ferroptosis-related markers, a reduced MMP, and an increased ROS was observed in cartilage tissues from OA patients vs. controls, IL-1β-stimulated chondrocytes vs. normal ones, and OA rat models vs. sham, so did miR-19b-3p. OA-FLS exosomes promoted MDA, Fe2+, ACSL4, and ROS but reduced cell viability, GSH/GSSG, GPX4, SLC7A11, and MMP in IL-1β-stimulated chondrocytes, whose effect was enhanced by miR-19b-3p mimics and attenuated by miR-19b-3p inhibitors. miR-19b-3p negatively regulated SLC7A11 and directly bound to SLC7A11 via luciferase reporter gene assay. Furthermore, SLC7A11 overexpression weakened miR-19b-3p mimics’ effect on ferroptosis-related markers, MMP, or ROS in IL-1β-stimulated chondrocytes. OA-FLS exosomes also induced cartilage damage and ferroptosis in OA rats whose influence was tempered by miR-19b-3p inhibitors. Conclusion OA-FLS exosomal miR-19b-3p enhances cartilage ferroptosis and damage by sponging SLC7A11 in OA, indicating a potential linkage among synovium, cartilage, and ferroptosis during the OA process.